Determinan Kepatuhan Diet Pada Pasien Hipertensi Yang Menjalani Perawatan Di Rumah Sakit Mitra Medika Medan - Sri lasmawanti; Afina Muharani Syaftriani; Maria Haryanti Butar butar (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Hypertension is a major global public health problem that requires comprehensive management, including long-term lifestyle modification and dietary regulation. Adherence to a recommended diet plays an essential role in controlling blood pressure and preventing cardiovascular complications; however, compliance is often influenced by psychosocial factors such as family support and therapeutic communication. This study aimed to identify the relationship between family support, therapeutic communication, and dietary adherence among patients with hypertension hospitalized at Mitra Medika Hospital Medan. An analytical survey with a cross-sectional design was conducted involving 46 hypertensive patients selected using accidental sampling. Data were collected through questionnaires assessing family support, therapeutic communication, and dietary adherence. Statistical analysis was performed using the chi-square test with a 95% confidence level. The results showed that 76.1% of respondents received supportive family support and 58.7% were compliant with the hypertension diet. A significant relationship was found between family support and dietary adherence (p = 0.005), indicating that patients with supportive families were more likely to comply with dietary recommendations. In addition, therapeutic communication was significantly associated with dietary adherence (p = 0.047), suggesting that effective communication between healthcare providers and patients enhances compliance. These findings highlight the crucial role of both family involvement and therapeutic communication in promoting dietary adherence among hospitalized patients with hypertension. Strengthening family participation and improving communication strategies by health professionals may improve treatment outcomes and support sustainable lifestyle changes. Integrating family-centred education and patient-focused communication into hypertension management programs is therefore strongly recommended to enhance adherence and reduce the risk of complications.